Peningkatan Kualitas Komoditas Kopi Organik dari Perkebunan dalam Perspektif Ekonomi Islam di Desa Srimenanti Lampung Barat - Refki Ferdiansyah; Rahmahwaty; Ekawati, Farida (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2025)
This study aims to improve the quality of organic coffee commodities from Srimenanti Village, West Lampung, through an Islamic economic approach. West Lampung is known as one of the largest coffee-producing regions in Lampung Province, making this commodity a major pillar of the local economy. Within the framework of regional development and the strengthening of the community’s economy, this research highlights the importance of applying Islamic economic principles such as justice, mutual assistance, and sustainability in coffee plantation management. The methods used in this study include a participatory approach through the identification of farmer and farmer group characteristics, skill enhancement training, and value-added analysis of various coffee processing methods. The results show that the natural anaerobic processing method provides the highest added value compared to other methods. Additionally, the involvement of the Women Farmers Group (Kelompok Wanita Tani/KWT) plays a significant role in improving the production and marketing of locally branded coffee known as KOROLA (Kopi Hitam Lampung Barat). This study confirms that the implementation of organic farming systems, capacity building for farmers, and the strengthening of cooperative institutions can create a sustainable farming ecosystem aligned with sharia principles. By integrating Islamic values into coffee management, it is expected that a balance between economic profit and social welfare can be achieved.